Re-operation of idiopathic macular hole after failed initial surgery - Hejsek, Libor; Dusova, Jaroslava; Stepanov, Alexandr; Rozsival, Pavel (Biomedical papers, 2014)
Background: Persistent idiopathic macular hole (IMH) after initial pars plana vitrectomy (PPV) appears in approx. 12% of cases. It is, therefore, one of the most common complications. IMH re-operation results tend to be better in eyes where IMH had been closed, while IMH re-operations in cases when the initial surgery had failed tend to be less successful: IMH often becomes even larger and visual acuity decreases, anatomical success rate of closure is about 60% and the resulting postoperative visual acuity is about 20/100.Aims: To establish anatomical and functional success rate of repeated operations of recurrent idiopathic macular hole.Materials and Methods: We evaluated the retrospective results of re-operations of persisting IMH that is cases in which the initial surgery did not result in closure: 6 eyes in 6 patients out of the overall 55 operated on IMH (primary PPV failed in almost 11% of cases). The follow-up period was 18 months (since the first surgery).Results and Conclusion: After the second PPV, the IMH was closed in 100% of operated eyes. It was not necessary to perform a third PPV during the follow-up period. In all cases the visual acuity improved. Anatomical and functional results of IMH treatment can be considered satisfactory. We consider the following combination of factors significant for the anatomical success rate of PPV: IMH size and stage, technical precision of the ILM peeling and the suction of the IMH contents, strict adherence to the recommended head positioning in early postoperative period, and IMH duration.
Keywords: recurrent macular holes; re-operation; pars plana vitrectomy